STAKEHOLDERS’ ENGAGEMENT AND SUSTAINABLE GROWTH OF LISTED FIRMS IN NIGERIA (Journal of Global Accounting, 2024)
This study empirically investigated the effect of customers’ protection and government taxation on sustainable growth of firms in Nigeria. Two hypotheses were formulated to guide the investigation and the statistical test of parameter estimates was conducted using panel least squares regression model. Ex Post Facto design was adopted and data for the study were obtained from the Nigerian Exchange Group Factbook and published annual financial reports of listed consumer goods firms on Nigerian Exchange Group (NGX) with data spanning from 2013-2022. The results of the study shows that government taxation and customers’ protection have positive and significant effect on sustainable growth of listed consumer goods firms in Nigeria. Thus, the study concludes that stakeholders’ engagement ensures corporate sustainable growth in Nigeria. The study therefore recommends that firms should accept and treat customers’ complaints with utmost priority and also create room for customers review in order to protect their interest which determines customers’ loyalty that invariably ensures firm sustainable growth. Also, managers of listed firms should pay their corporate taxes as and when due without any form of evasion as it’s through corporate taxes that government provide enabling environment and friendly laws for business sustainability in Nigeria.
Keywords: Consumer Protection; Government Taxation; Stakeholders Engagement